Lung ultrasound for volume status assessment in chronic hemodialysis patients - Ivanov, Igor; Veselinov, Vladimir; Ćelić, Dejan; Dejanović, Jadranka; Obradović, Dušanka; Knežević, Violeta (Vojnosanitetski pregled, 2021)
Backoground/Aim. Assessing volume status in chronic hemodialysis (HD) patients is difficult despite several techniques have been developed. The aim of this study was to demonstrate the adequacy and efficacy of lung ultrasound (LUS) and B line score (BLS) in the assessment of volume status in patients on HD in comparison to other techniques: ultrasonographic determination of inferior vena cava diameter (IVCD), echocardiography (ECHO) and B-type natriuretic peptide (BNP) determination. Methods. LUS, ECHO, ultrasonography of inferior vena cava in inspiration (IVCDi) and expiration (IVCDe), and BNP sampling were performed before and after HD in 83 patients. Results. A significant reduction of BLS, IVCDi, IVCDe, BNP and several ECHO parameters such as left atrium diameter (LA), left ventricular internal dimension in diastole and systole (LVIDd and LVIDs, respectively), and left atrial volume in systole (LAVs), was registered (p < 0.001). There was a significant correlation between BLS and BNP before (p = 0.01) and after HD (p = 0.05), and a weaker but significant correlation between BLS and IVCDi and IVCDe before HD (p = 0.05). Conclusion. All techniques assessed hypervolemia before and after HD successfully. BNP correlated with LUS before and after HD, and IVCDi and IVCDe correlated with LUS only before HD. LUS is cheap and simple to perform, can be performed bedside and can be reliably used for assessing volume status in HD patients.
Keywords: renal hemodialysis; lung; ultrasonography; natriuretic peptide, brain; vena cava, inferior; echocardiography; water-electrolyte imbalance